ОИЛАДА РЕПРОДУКТИВ ХУЛҚНИНГ ПСИХОЛОГИК ЖИҲАТЛАРИ - Каландарова, М.Б. (SCIENCE and SOCIETY, 2019)
In the following article, social-psychological features of reproductive behavior in the family are discussed.